FRI0104 Cohort study of infectious disease risk management in RA patients receiving tocilizumab at 48 weeks (ACT4U-study48). (23rd January 2014) - Ihata, A.; Hagiyama, H.; Nagaoka, S.; Obata, J.; Miyachi, K.; Yamada, H.; Hirohata, S.; Koido, N.; Yamasaki, M.; Miyagi, K.; Ohno, S.; Kishimoto, D.; et al.
Abstract : Background: An administration of tocilizumab (TOC) rapidly reduced inflammatory markers such as CRP and ESR, which made the diagnosis of infection difficult. According to PMS for 28 weeks, 553 events of infection and 163 events of serious infection (SI) were reported. There is a real need for the reduction of the infection risk. Objectives: To validate the deterrence effect of infectious disease risk management (IDRM) in RA patients with TOC. Methods: Forty-nine RA patients with TOC were enrolled from 4 universities and affiliated clinics. They were required to comply with IDRM policy during observation period. Primary endpoint was an occurrence frequency of SI (OFSI). Results: Although 17 events of infection and 3 events of SI were observed, neither pneumonia nor cellulitis occurred. Risk factors were 10 year over disease duration and 5mg over CS dosage at the baseline. CDAI was changed from 61.1±3.7 to 18.3±4.4. The dose of CS was reduced by 41.8%. Persistence rate of TOC was 69.4% at 48 weeks. Conclusions: In spite of higher frequency of concomitant lung disease, the incidence of respiratory infection and OFSI were lower in our study than PMS. IDRM could contribute to reduction of OFSI especially in respiratory infection. References: Koike T, et al. Ann Rheum Dis 2011:70:2148-2151 Disclosure of Interest: None Declared